Does Gender Inequality Lead to Income Inequality? Evidence from Indonesia - Lilis Siti Badriah; Istiqomah Istiqomah (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
The study purpose is to analyze the effect of gender inequality in education, health, and labor force participation on income inequality in Indonesia.  Data from 33 provinces in Indonesia during 2011-2018 were analyzed with panel data regression. The results show that gender inequality in education and labor force participation has a negative and significant effect on income inequality. However,  gender inequality in life expectancy does not affect income inequality. The implications are the government should provide free education in poor regions such as by providing a larger allocation of scholarship funds  and create employment programs to reduce education as well as income inequality, government. In this case,the government can expand community empowerment programs accompanied by intensive and sustainable assistance  and private sector should open the widest possible job opportunities without gender discrimination. This research contributes to development economics, particularly regarding the problem of gender inequality and income inequality  where it is found that income inequality is influenced by the occurrence of gender inequality both in terms of education and work participation. Previous studies have examined the relationship between gender inequality and economic growth, while this study analyzes the relationship between gender inequality and income inequality based on provincial data in Indonesia. Apart from gender inequality, this study also analyzes two control variables: government capital expenditure and income per capita.